The headteachers' perception of practicing of effective transformational leadership, Malaysia - Salleh, Mohamad Johdi; Saidova, Parvina (2010)
The study discusses the headteachers’ perceptions of practicing of effective transformational leadership in primary schools Malaysia. This study focuses on four dimensions of transformational leadership namely a developing widely shared vision, providing intellectual stimulations, offering individualized support, and, creating a productive school culture. The study used questionnaire to collect data from a conveniently and randomly selected sample of one hundred and seventy six headteachers pursuing the special Bachelor of Educational Management program at the International Islamic University Malaysia (IIUM), University Malaysia Sabah (UMS); University Tun Hussein Onn Malaysia (UTHM). The result of the analysis showed that practice and effectiveness of transformational leadership were correlated positively according to respondents’ perception. For practice and effectiveness, r=.725, p<.000. This means, there was a strong association or relationship between practice and effectiveness according to respondents’ perception. In general, as it was perceived by headteachers the effectiveness of transformational leadership depends on practicing it. It means the headteachers who practiced transformational leadership frequently or moderately often perceived it as effective.